Wrist actigraphic assessment of sleep in 116 community based subjects suspected of obstructive sleep apnoea syndrome. Issue 3 (March 1995) - Middelkoop, H A; Knuistingh Neven, A; van Hilten, J J; Ruwhof, C W; Kamphuisen, H A
Abstract : BACKGROUND–The combined use of wrist actigraphic assessment and self assessment of sleep in the screening of obstructive sleep apnoea syndrome was evaluated in a community based sample. METHODS–One hundred and sixteen community based subjects clinically suspected of having obstructive sleep apnoea (syndrome) were evaluated by means of simultaneous ambulatory recording of respiration (oronasal flow thermistry), motor activity (wrist actigraphy), and subjective sleep (sleep log) during one night of sleep. RESULTS–The subjects were distributed according to their apnoea index (AI); AI < 1 (non-apnoeic snorers) 44%; AI 1- < 5 39%; and AI > or = 5 17%. High apnoea index values were associated with self reported disturbed sleep initiation and more fragmented and increased levels of motor activity and decreased duration of immobility periods, particularly in those with an apnoea index of > or = 5. Across subjects the duration of immobility periods was the only predictor of the apnoea index, explaining 11% of its variance. Use of the multiple regression equation to discriminate retrospectively between those with an apnoea index of < 1 and > or = 5 resulted in sensitivity and specificity values of 75% and 43%, and 5% and 100%, respectively. CONCLUSIONS–The combined use of a sleep log and actigraphic assessment of sleep failed to identify reliably those subjects who suffered from obstructive sleep apnoea (syndrome) in a sample of community based subjects reporting habitual snoring combined with excessive daytime sleepiness and/or nocturnal respiratory arrests.